Measuring Concentration of the Banking Market of the Republic of Croatia - Fran Galetić; Tena Obradović (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
Over the last twenty years, Croatian banking market has been extremely dynamic in terms of market concentration. The #of banks was cut in half, and more often than ever, the banks are entering the processes of mergers and acquisitions. In this paper we calculate nine different indices of concentration. Today, there are 26 commercial banks in Croatian banking market, which has the elements of both, oligopoly and monopolistic competition. Indices that contribute to the larger banks lead the conclusion toward oligopoly, however indices that emphasize the importance of smaller banks point out moderate and even low concentration. From 2000 till today, the #of banks was cut in half which resulted in the increase of concentration on the banking market. This trend is also expected in the future due to increased mergers and acquisitions.
Keywords: 650; Market concentration; Banking market; Measures of concentraiton